Chronic thromboembolic pulmonary arterial hypertension: a review of the literature and novel therapeutic approaches. (June 2015) - Androulakis, Emmanuel; Lioudaki, Eirini; Christophides, Theodoros; Ahmad, Mahmood; Fayed, Hossam; Laskar, Nabila; Schreiber, Benjamin
Abstract : Chronic thromboembolic pulmonary hypertension is defined as pulmonary hypertension (PH) caused by single or recurrent pulmonary emboli and is characterized by chronic obstruction of the pulmonary arteries leading to increased vascular resistance and PH. Also, progressive remodeling may occur in occluded and nonoccluded territories. Better understanding of the underlying mechanisms and risk factors could improve diagnosis and allow appropriate interventions. Pulmonary endarterectomy is an established approach and is considered the definitive treatment for chronic PH, resulting from thromboembolic disease. Furthermore, percutaneous transluminal pulmonary angioplasty is technically feasible, especially for those with peripheral-type of the disease. In addition, several agents, including prostanoids, endothelin receptor antagonists and phosphodiesterase type-5 inhibitors, have been tested in selected patients yielding promising results. Several novel agents are under investigation, and extensive research is currently in progress aiming to resolve uncertainties in the understanding and treatment of the disease.